Democratization without representation : the politics of small industry in Mexico - Shadlen, Kenneth C. (Pennsylvania State University Press, 2004)
When countries become more democratic, new opportunities arise for individuals and groups to participate in politics and influence the making of policy. But democratization does not ensure better representation for everyone, and indeed some sectors of society are ill-equipped to take advantage of these new opportunities. Small industry in Mexico, Kenneth Shadlen shows, is an excellent example of a sector whose representation decreased during democratization. Shadlen's analysis focuses on the basic characteristics of small firms that complicate the process of securing representation in both authoritarian and democratic environments. He then shows how increased pluralism and electoral competition served to exacerbate the political problems facing the sector during the course of democratization in Mexico. These characteristics created problems for small firms both in acting collectively through interest associations and civil society organizations and in wielding power within political parties. The changes that democratization effected in the structure of corporatism put small industry at a significant disadvantage in the policy-making arena even while there was general agreement on the crucial importance of this sector in the new neoliberal economy, especially for generating employment. The final chapter extends the analysis by making comparisons with the experience of small industry representation in Argentina and Brazil. Shadlen uses extensive interviews and archival research to provide new evidence and insights on the difficult challenges of interest aggregation and representation for small industry. He conducted interviews with a wide range of owners and managers of small firms, state and party officials, and leaders of business associations and civil society organizations. He also did research at the National Archives in Mexico City and in the archives of the most important business organizations for small industry in the post-World War II period.